Public-private partnership development in Southeast Asia - Fauziah Zen (Asian Development Bank (ADB), 2018)
Infrastructure development in Southeast Asia has been financed mainly by public funds, which leave wide gaps in majority of countries. Governments have tried to attract the private sector by offering various schemes under public-private partnership (PPP). Typically, PPP contributes less than 1% of gross domestic product, while public finance greatly varies from about 2% to 10% of a country's gross domestic product. Among major factors supporting PPP implementation, the following features are critical: coherent policy, public sector capacity to manage PPP appropriately, public sector willingness to have mutual relation with private partners, and leadership. Private participation is still continuously growing; and its implementation is not limited to hard infrastructure only, but also to social infrastructure.
Keywords: H54; O21; R53; 330; infrastructure development; private sector participation; public-private partnership; social infrastructures